Kekosongan Hukum Terhadap Kreditor Yang Tidak Mau Menyerahkan Harta Yang Terdaftar dalam Boedel Pailit (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
An application for bankruptcy will be granted by the commercial court provided that it has been found that at least two creditors have been found and that there is at least one bill that is due and can be billed which can be submitted voluntarily or involuntarily. The declaration of bankruptcy on the debtor has been decided by the commercial court will result in the debtor losing his rights and control in managing and controlling all his assets. In this case, the bankrupt debtor will be controlled by the curator under the supervision of a supervisory judge. The curator has the task of recording the assets and matching the receivables owned by the debtor. It is often found in practice that assets have been transferred to third parties or even creditors. When the debtor goes bankrupt and asks to return the assets, the parties definitely refuse to hand over so that this causes losses for other creditors. The purpose of writing this journal is for knowledge and assessment of the regulations that have been applied. The research method used is normative research with a conceptual, statutory and comparative approach and uses secondary data as a reference. The discussion in this paper discusses the legal arrangements regarding the transfer of assets registered in the bankruptcy bank and legal remedies that can be taken by the curator so that the assets registered in the bankrupt bank but do not want to be handed over by creditors can be liquidated. The conclusion is that although there has been a regulation regarding the surrender of bankrupt boedel assets, but without any sanctions, the implementation is uncertain and the effort that can be made by the curator is to apply for the cancellation of the legal action that has arisen.